2020
DOI: 10.1094/phyto-03-19-0077-r
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Acquisitions in Emerging Populations ofXanthomonas vasicolapv.vasculorumInfecting Corn in the United States and Argentina

Abstract: Xanthomonas vasicola pv. vasculorum is an emerging bacterial plant pathogen that causes bacterial leaf streak on corn. First described in South Africa in 1949, reports of this pathogen have greatly increased in the past years in South America and in the United States. The rapid spread of this disease in North and South America may be due to more favorable environmental conditions, susceptible hosts and/or genomic changes that favored the spread. To understand whether genetic mechanisms exist behind the recent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
1
17
0
1
Order By: Relevance
“…Collectively, these findings further reinforce the hypothesis that Ethiopia is the centre of diversity of Xvm, and possibly its area of origin. Nevertheless, this pathovar remains apparently relatively monomorphic, with no more than a few hundred SNPs distinguishing any two isolates, significantly fewer than that observed in another pathovar of the same species (Aritua et al, 2007; Wasukira et al, 2014; Perez‐Quintero et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Collectively, these findings further reinforce the hypothesis that Ethiopia is the centre of diversity of Xvm, and possibly its area of origin. Nevertheless, this pathovar remains apparently relatively monomorphic, with no more than a few hundred SNPs distinguishing any two isolates, significantly fewer than that observed in another pathovar of the same species (Aritua et al, 2007; Wasukira et al, 2014; Perez‐Quintero et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…The Xvv strain Xv1601, a pathogen of maize, was used for delivery, and, based on previous sequence analysis, is free of TALe genes (Perez-Quintero et al, 2020). Phylogenetic analysis of 10 Xanthomonas species indicated that Xvv is genetically close to Xanthomonas oryzae (Xo) ( Supplemental Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we used TALe-mediated targeting activation of transcription as delivered by the maize pathogen Xanthomonas vasicola pv. vascularum (Xvv) (Perez-Quintero et al, 2020) to characterize the regulation of cuticular wax development. Cuticular waxes are derivatives of very-long-chain fatty acids (VLCFAs), which are produced through cyclic reactions that add two carbons per cycle (Kunst and Samuels, 2003; Lee and Suh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We previously produced a genome assembly of an Xvv isolate Xvv1601 that was isolated from a Kansas corn adult leaf showing the symptoms characteristic of bacterial leaf streak in 2016 ( 33 ). PacBio long reads were used for the genome assembly with the assembler Canu ( 26 ).…”
Section: Resultsmentioning
confidence: 99%